Double-bottom antimicrobial packaging for apple shelf-life extension. (1st May 2019) - da Rocha Neto, Argus Cezar; Beaudry, Randolph; Maraschin, Marcelo; Di Piero, Robson Marcelo; Almenar, Eva
Highlights: Created a double-bottom antimicrobial package that extends apple shelf life. The novel package slows Penicillium expansum growth. The novel package reduces apple ethylene production, respiration rate and firmness loss. Double-bottom antimicrobial packages with ICsa extend apple shelf life better than with ICp. A new strategy to reduce postharvest losses in countries lacking cold storage. Abstract: A package was created that extends apple shelf-life by slowing Penicillium expansum growth. The package consisted of a peelable lid and a tray with a double bottom with inclusion complexes (ICs) of ß-cyclodextrin (ß-CD) containing the essential oils of palmarosa (ICp) or of star anise (ICsa). Oil amounts required for antimicrobial activity were obtained from in vitro assays. After 12 days at 23 °C, P. expansum -inoculated apples in both of the double-bottom antimicrobial packages (DBAP) had 1/3 less fungal growth, less than 50% weight loss and ethylene and CO2 production, and less than 25% firmness loss, TA and SSC increase, and pH decrease compared to controls. The DBAP with ICsa performed better than with ICp in reducing ethylene production, respiration rate, firmness loss, TA increase, and pH decrease. This demonstrates DBAP containing ICp or ICsa can maximize the shelf-life of apples injured by P. expansum, validating a novel type of antimicrobial packaging.